Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Dobbs, Stephen C.; Paull, Charles K.; Lundsten, Eve M.; Gwiazda, Roberto; Caress, David W.; McGann, Mary; Coholich, Marianne M.; Walton, Maureen A. L.; Nieminski, Nora M.; McHargue, Tim; Graham, Stephan A. (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.